The Effects of Bibliotherapy and Equine - Assisted Therapy on Traumatized Children - Jūratė Sučylaitė; Donata Grakauskaitė-Šličienė (Lithuanian Sports University, 2020)
Background. Early childhood traumas leave serious consequences: during adolescence and adulthood people often experience internal conflicts, more often suffer from mental and somatic diseases, so it is important to look for therapies that can neutralize or reduce the effects of early traumas. One of the options is to apply a complex of bibliotherapy and equine assisted therapy. However, there is a lack of studies analysing how these two therapies affect the development. The aim was to explore the influence of bibliotherapy and equine-assisted therapy on the emotions and behaviour of children with early trauma. Methods. Qualitative research used interview, observation, and projection techniques. Results. Bibliotherapy created preconditions for the emergence of repressed feelings and for deeper, more sensitive dialogue with the psychologist. Riding helped to relax, captured the attention of the present, strengthened positive emotions. Conclusions. 1. Equine - assisted therapy affects the body and gives positive emotions, reduces child's inner anxiety, improves mood and consolidates bibliotherapy results. 2. The combination of bibliotherapy and equine - assisted therapy creates the conditions for stabilizing and even transforming the negative emotions of children with early trauma and restoring the fullness of childhood life. Keywords: psychological trauma, child development, emotions, horse assisted therapy, bibliotherapy.